2005
DOI: 10.1016/j.eiar.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of computer modelling in participatory integrated assessments

Abstract: In a number of recent research projects, computer models have been included in participatory procedures to assess global environmental change. The intention was to support knowledge production and to help the involved non-scientists to develop a deeper understanding of the interactions between natural and social systems. This paper analyses the experiences made in three projects with the use of computer models from a participatory and a risk management perspective. Our cross-cutting analysis of the objectives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…On the other hand, the majority of studies on PM activities arrive at the conclusion that to be accepted and used by stakeholders, models employed in PM should be simple, robust, and easy to use (e.g., Horlitz 2006;Janssen et al 2008;Kok et al 2008;Siebenhüner and Barth 2007;Webler and Tuler 2006). Without attempting to discuss the controversial issue of complexity/simplicity of models any further, we can also mention that many authors observe a coupling between uncertainty and complexity (Hare 2011; Krysanova et al 2007;Van Asselt and Rotmans 2002;Volk et al 2010).…”
Section: Discussion: Challenges Of Pm In Research On Global Change Immentioning
confidence: 99%
“…On the other hand, the majority of studies on PM activities arrive at the conclusion that to be accepted and used by stakeholders, models employed in PM should be simple, robust, and easy to use (e.g., Horlitz 2006;Janssen et al 2008;Kok et al 2008;Siebenhüner and Barth 2007;Webler and Tuler 2006). Without attempting to discuss the controversial issue of complexity/simplicity of models any further, we can also mention that many authors observe a coupling between uncertainty and complexity (Hare 2011; Krysanova et al 2007;Van Asselt and Rotmans 2002;Volk et al 2010).…”
Section: Discussion: Challenges Of Pm In Research On Global Change Immentioning
confidence: 99%
“…Indeed, several recent initiatives are attempting to integrate qualitative knowledge forms that are dynamic within stakeholder and partner communities into the parameterisations, structure and outputs of formal quantitative models (e.g. Siebenhüner and Barth, 2005;TIA, 2007; the UEKC project: Lane et al, 2011;Odoni and Lane, 2010;Whatmore and Landstrom, 2011). As these studies argue,…”
Section: Comprehensibility and Communicationmentioning
confidence: 99%
“…Although, as the case studies have demonstrated, it is argued that participatory GIS cannot be effective on its own, there is strong international support for the use of GIS as a complementary tool in public participation processes (González et al, 2008b). However, the apparent risk to the interests of developers, assessors or decision-makers influencing the filtering and representation of spatial information (Towers, 1997;Harrison and Haklay 2002;Siebenhüner and Barth, 2004) needs to be carefully addressed. Information manipulation was apparent in the Mayo CDP website, where fear of disclosure affected the comprehensiveness of the information conveyed to the public and, as a result, the scope and validity of public consultation.…”
Section: Optimising Framework Conditionsmentioning
confidence: 99%